Introduksi Varietas Unggul Jagung Untuk Mendukung Pengembangan Jagung di Kabupaten Kutai Kartanegara - Wawan Banu Prasetyo (Jurnal Riset Agribisnis dan Peternakan, 2018)
Corn is an alternative foodstuff to be developed as a supporter of food diversity policies, especially seen from its position as the main source of carbohydrates and protein after rice. New superior varieties (VUB) is one component that plays an important role in efforts to increase corn productivity. The introduction of corn VUB in East Kalimantan was carried out to increase corn productivity above the average of more than 45.42 Ku/ha, which was carried out in two 2012-2014 planting seasons in Kutai Kartanegara Regency. There are five varieties introduced in the dry land of Kutai Kartanegara. The new superior varieties (VUB) used are hybrid Bima 3, 9, and 19, while the composite corn is Sukmaraga and Lamuru. From the adaptation test results, the average productivity in each variety varies: (1) Bima 3 productivity 7,795 tons of shelled / ha, (2) Bima 9 productivity 4.54 tons of shelled / ha, (3) Bima 19 productivity 7.24 tons of shelled / ha, (4) Sukmaraga productivity of 6,515 tons of shelled / ha, (5) Lamuru productivity of 7.69 tons of shelled / ha, The results of the introduction show that using VUB can increase productivity by 31.66 - 42.10% compared to without using VUB